Customer Relationship Management PT Agrapana Wukir Panca - Diana Ari Suryaningsih (Publikasi Indonesia, 2022)
Customer Relationship Management (CRM) is a process in building and improving company and customer relationships with the aim of increasing customer loyalty to purchases. This research uses the documentation method. The documentation method is a source of data in the form of sources from images or videos, works, and written things that can provide information. Based on the research results, PT Agrapana Wukir Panca is a company whose legalization status is still in the form of a Trade Unit, therefore Customer Relationship Management is needed. Customer Relationship Management itself is a process in improving or building relationships between companies and customers, to instill customer loyalty in making purchases. The component frameworks for Customer Relationship Management are operational CRM, analytical CRM, and collaborative CRM. The conclusion of this study is that Customer Relationship Management (CRM) has a framework of components and approaches that companies can take to maintain and develop customer relationships. And has benefits including: Encouraging customer loyalty, reducing costs, increasing operational efficiency, increasing time to market, and increasing revenue.